Analisis Usaha Tani Padi dengan Pola Rotasi Tanaman Padi-Padi-Kacang Tanah dan Pola Rotasi Tanam Padi-Padi-Jagung (Studi Kasus di Desa Mojokrapak Kecamatan Tembelang Kabupaten Jombang) - Ika Rahmatin Nahdia; Siti Nur Qomariyah; Agus Suhadi (KOLONI, 2023)
The purpose of this study was to find out how much income rice farming has with the rice-rice-peanut cropping pattern and the rice-rice-corn cropping pattern in Mojokrapak Village, Tembelang District, Jombang Regency. This research was conducted in March 2022 in Mojokrapak Village, Tembelang District, Jombang Regency. The samples taken in this study were rice farmers using the rice-rice-peanut cropping pattern with a total of 20 farmers and 20 farmers using the rice-rice-corn cropping pattern. Taking into account the number of rice farmers in the area there are 206 farmers, and farmers who use the rice-rice-peanut cropping pattern are 20 people, by means of interviews using a questionnaire. Data analysis techniques using descriptive quantitative methods. The results showed that the income of farmers with the rice-paddy-peanut planting system was Rp. 74,036,084, while the farmers with the rice-rice-corn planting pattern was Rp. 55,607,778.54,-. The magnitude of the R/C ratio of rice farmers with the rice-rice-peanut planting pattern is 2.37 while the farmers with the rice-rice-corn planting pattern is 2.14, while based on the results of the analysis of the calculation of the B/C ratio, the feasibility level of rice farming in the village is obtained. Mojokrapak in 2022 rice farmers with a rice-rice-peanut planting pattern are 1.37 while farmers with a rice-rice-corn planting pattern are 1.14.